Environmental Effects of Generator Fumes in Kwara State, Nigeria: A Survey- An Empirical Evidence - Saka, Abdulrasaki (Archives of Business Research, 2021)
In March 2019 the Nigeria, Tertiary Education Trust Fund (TETFUND) funded a proposal I submitted to conduct a research project aimed at determining the quantitative magnitude impact of environmental effects of generator fumes in Kwara State, Nigeria. This paper assesses the impact of this energy use and measure on health hazards, environmental damage and social hazards, using households and business owners as the key units of analyses. Our findings indicate that affected users reacted heterogeneously to the effects of fossil-fuels-electric-generator which releases generator fumes from its exhaust pipe. Specifically, data analyzed were sufficiently adequate to reveal its significance that an increase in neighbors’ exposure to hazards by 1 unit reduces generator fumes by about 6 per cent; whereas an increase in health hazards (impaired visibility, deafness, sleeplessness, choking sensation and dizziness), and noise pollution (environmental hazards), by 1 unit increases generator fumes by about 9%; and an increase by one unit of parent/s who are usually followed by their wards to start fossil-fuels-electric-generator increases generator fumes by about 5% (0.046), holding all other factors constant. As expected, the impacts of the measure on the use of fossil-fuels-electric-generator has been rather serious in health and environmental concerns.